Online dosimetric evaluation of larynx SBRT: A pilot study to assess the necessity of adaptive replanning. (22nd December 2016) - Mao, Weihua; Rozario, Timothy; Lu, Weiguo; Gu, Xuejun; Yan, Yulong; Jia, Xun; Sumer, Baran; Schwartz, David L.
Abstract: Purpose: We have initiated a multi‐institutional phase I trial of 5‐fraction stereotactic body radiotherapy (SBRT) for Stage III–IVa laryngeal cancer. We conducted this pilot dosimetric study to confirm potential utility of online adaptive replanning to preserve treatment quality. Methods: We evaluated ten cases: five patients enrolled onto the current trial and five patients enrolled onto a separate phase I SBRT trial for early‐stage glottic larynx cancer. Baseline SBRT treatment plans were generated per protocol. Daily cone‐beam CT (CBCT) or diagnostic CT images were acquired prior to each treatment fraction. Simulation CT images and target volumes were deformably registered to daily volumetric images, the original SBRT plan was copied to the deformed images and contours, delivered dose distributions were re‐calculated on the deformed CT images. All of these were performed on a commercial treatment planning system. In‐house software was developed to propagate the delivered dose distribution back to reference CT images using the deformation information exported from the treatment planning system. Dosimetric differences were evaluated via dose‐volume histograms. Results: We could evaluate dose within 10 minutes in all cases. Prescribed coverage to gross tumor volume (GTV) and clinical target volume (CTV) was uniformly preserved; however, intended prescription dose coverage of planning treatment volume (PTV) was lost in 53% of daily treatments (mean: 93.9%, range: 83.9–97.9%). Maximum bystander point dose limits to arytenoids, parotids, and spinal cord remained respected in all cases, although variances in carotid artery doses were observed in a minority of cases. Conclusions: Although GTV and CTV SBRT dose coverage is preserved with in‐room three‐dimensional image guidance, PTV coverage can vary significantly from intended plans and dose to critical structures may exceed tolerances. Online adaptive treatment re‐planning is potentially necessary and clinically applicable to fully preserve treatment quality. Confirmatory trial accrual and analysis remains ongoing.